Road Safety Awareness and Attitudes Among Undergraduate Students in a City of Western India - Christian, Donald S; Thakkar, Rishika K (Indian Journal of Community Health, 2025)
Background: Road traffic injuries (RTIs) pose a major global public health challenge, causing significant morbidity, mortality and disability annually. India, despite having only 1% of the world’s vehicles, contributes significantly to global road fatalities. Factors such as poor road conditions, inadequate driver training, lax enforcement of traffic laws, and risky driving behaviors exacerbate the issue. Young adults, due to their mobility and risk-taking tendencies, are particularly vulnerable. This study aimed to assess the awareness, attitudes, and behaviors of undergraduate students in Ahmedabad regarding road safety. Methods: A cross-sectional study was conducted among undergraduate students across five academic disciplines in Ahmedabad during the 2021–2022 academic year. A multistage random sampling method was employed, selecting colleges from different administrative zones. A structured questionnaire was administered online via Google Forms. The sample size was determined at 440 students, with additional considerations for non-response. Descriptive statistical methods, including Chi-square tests, were used to analyze the data. Results: The study included 446 respondents (51.3% males, 48.7% females) with a mean age of 20.84 years. Most students drove both two- and four-wheelers (52.2%), while 30.7% drove only two-wheelers. A majority (90.3%) held valid driving licenses. Risky behaviors such as underage driving (14.1%), use of mobile phones while driving (56.8% Bluetooth, 8.5% handset), and non-compliance with protective gear (39.5% always, 9.9% never) were noted. Over speeding and distracted driving were identified as significant accident contributors. A substantial proportion of respondents (59.2%) supported stricter enforcement of traffic laws. Conclusion: The findings highlight critical gaps in road safety awareness and behavior among undergraduate students. While most students recognize the dangers of reckless driving, non-compliance with safety measures remains prevalent. Strengthening road safety education, promoting responsible driving behaviors, and enforcing stricter regulations are essential to reducing RTIs among young adults.